Justification of post-ratcheting hardening behavior of annealed Copper through hardening coefficient and hardening factor. (2020) - Mahato, Jayanta Kumar; De, Partha Sarathi; Anand, Kumar Aniket; Kundu, Amrita; Chakraborti, P.C.
Abstract: The present research work has been carried out to investigate the ratcheting behavior at different stress ratios under constant maximum stress and changes in post-ratcheting tensile properties of commercially pure (99.97%) polycrystalline Copper. All the ratcheting tests were done at room temperature upto 25% true ratcheting strain accumulation. After ratcheting deformation tensile tests were performed on ratcheted specimens at strain rate of 10 −3 s −1 up to complete fracture. Post-ratcheting hardening behaviors were analyzed by the variation of plastic strain amplitude and hardening factors with respect to number of cycles. It is observed that the number of cycles over which a constant amount of ratcheting deformation occurs exponentially increases with increase of stress ratio. It is also observed that post ratcheting tensile properties of annealed copper linearly increases with increase of stress ratio. Such observations of post-ratcheting hardening behavior have been successfully justified by the variation of hardening coefficient and hardening factor.